The Concept of "Perfect Man" and its axiological meaning (Eurasian Journal of Religious Studies, 2022)
The article discusses the concept of "Perfect Man", which has recently been revived in Kazakhstani society. The idea of ​​a perfect man, which originated with such Muslim thinkers as Ibn Arabi, occupies a special place in the teachings of Sufism and existed in the Kazakh steppes before Abai. The definitions of the concept of a perfect person by Muslim thinkers, the features of various aspects of this concept, the meaning in Sufism, the importance of revealing the general axiological value are given. To what extent can the concept of the “Perfect Man” contribute to the prevention of such problems of modern society as the loss of human qualities, religious intolerance, the loss of spiritual and moral values, human degradation, and so on? Along with the answer to this question, the image of a person deprived of humanity is considered, as well as the image of a spiritually filled person, their significance for society. Saying that the "Perfect Man" leads the world and society in the right direction, also condemns bad habits among people, but rather promotes order in the life of every person. Here, issues related to the formation of a new life were discussed in detail, thereby focusing on the background of a good knowledge of objects and phenomena. The task of a perfect person is to delve into the phenomena of the universe, to form life skills based on truth.Key words: Perfect Man, Ibn Arabi, tasawwuf, Muslim thinkers, Islam
Keywords: Perfect Man; Ibn Arabi; Tasawwuf; Muslim Thinkers; Islam